2021
DOI: 10.38025/2078-1962-2021-20-3-104-112
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training effectiveness and Tolerance in Patients after Myocardial Infraction, Depending on the Initial Physical activity Tolerance

Abstract: Aim. To investigate exercise tolerance in patients undergoing acute coronary syndrome with outcome in myocardial infarction, dependingon physical activity tolerance. Material and methods. We studied 80 patients aged from 40 to 75 years old who were admitted from primary vascular centers for athree-week rehabilitation course to the department of medical rehabilitation for patients with somatic diseases of the clinic of the IvanovoState Medical University of the Ministry of Health of Russia, of which 61 were men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In the actual analysis of the abovementioned relevant index data, the whole analysis process becomes more complicated due to the existence of certain connections between the variables. Therefore, it is necessary to use factor analysis to process the obtained data, simplify the analysis process, and make the analysis results simpler and clearer [ 15 ]. The specific process is as follows: First, the data that are determined to participate in factor analysis are sorted, then the R-type matrix of the relevant data is obtained, and the KMO moderate test and Bartlett's sphericity test are carried out on it.…”
Section: Methods For Improving Physical Fitness Of Athletes Taking Sp...mentioning
confidence: 99%
“…In the actual analysis of the abovementioned relevant index data, the whole analysis process becomes more complicated due to the existence of certain connections between the variables. Therefore, it is necessary to use factor analysis to process the obtained data, simplify the analysis process, and make the analysis results simpler and clearer [ 15 ]. The specific process is as follows: First, the data that are determined to participate in factor analysis are sorted, then the R-type matrix of the relevant data is obtained, and the KMO moderate test and Bartlett's sphericity test are carried out on it.…”
Section: Methods For Improving Physical Fitness Of Athletes Taking Sp...mentioning
confidence: 99%
“…3 The Wingate test was carried out 10 days before the training started, 14 athletes were ranked from high to low according to the relative value of maximum power (W/kg) measured and numbered from 1 to 14, two players with similar abilities were divided into one group, a total of 7 groups were obtained, using a paired design method, two athletes in each group were divided into a constant number of cycling group (CG) and a reduced number of cycling group (DG), with 7 athletes in each group. 4 Before the start of the study, the athletes were mainly explained the purpose and significance of the study, the procedures and precautions of each functional test and training, and familiarized themselves with the methods and steps of the test. The details of the research subjects are shown in Table 1.…”
Section: Methods Research Objectsmentioning
confidence: 99%